Kekuatan Bending Panel Komposit Lamina Berbasis Karung Plastik Bekas (Woven Bag) - Heri Yudiono; Samsudin Anis; P Pramono (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
Waste made from plastic, especially plastic sacks has become a national problem because of the intensity of its ever increasing use and the behaviour of the people who are less concerned about the environment, so as soon to find control efforts that are pro-environment, pro-technology and pro-economic. This research aims to analyze the bending strength, modulus of elasticity, and the degree of deflexivity of the lamina composite panels from used plastic sacks as an alternative material which is tough, lightweight, and strong. The research method used was an experimental method with the category of Pre-Experimental Designs type Static Group Comparations. The tests were conducted for the control groups and experimental groups. The experimental group is the group that is treated by varying the orientation of the used woven plastic sack fibers 0°/0°/0°/0°, 0°/+30°/0°/+30°, 0°/+45°/0°/+45°, 0°/+60°/0°/+60° and 0°/+90°/0°/+90°. The control group in this study were specimens that were not treated in the form of bumpers as product controls. The specimens of bending test are using the ASTM D790 standard. The results of the research reveal that the orientation of the fiber affects the bending strength of the lamina composite based on used plastic sacks. The highest bending strength in fiber orientation 0°/+60°/0°/+6°.. is 123.4 N/mm² and the that previous price is 24.96% higher than the bumper bending strength as a product control of 92, 6 N/mm². Debonding occurs on test specimens due to the release of bond in the contact area of the fiber-matrix caused by the shearing forces that the matrix cannot hold.